Analisis Daya Dukung Pada Wisata Buntu Burake, Kabupaten Tana Toraja, Provinsi Sulawesi Selatan - Sinay, Kaleb Yusuf; Mariati, Sri; Brahmantyo, Himawan; Rahmanita, Myrza (Jurnal Ilmiah Pariwisata; Vol 27 No 3 (2022): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v27i3.1623, 2022)
The Buntu Burake Destination is artificial. In the Buntu Burake area, a statue of Jesus Christ was built with a statue height of 45 meters that resembles the Christ the Redeemer Statue in Rio de Janeiro, Brazil. This study aims to analyze the carrying capacity of tourism in the tourist attraction of Buntu Burake. To achieve this goal, the authors use descriptive qualitative methods, with observations, in-depth interviews with key persons and tourists, literacy as a data collection method, and analysis using indicators of sustainable tourism development. UNWTO guidelines. The results of this study indicate that of the 29 indicators on the physical-ecological aspect, 66% was achieved, the socio-demographic aspect reached 88.5%, and the economic-political aspect was 67%. Ecological and political economy has a fairly good category. The results of the analysis of the carrying capacity of the Buntu Burake tourist destination have a value of 74% with a good enough category for sustainability. For this reason, it is necessary to improve the quality of tourism infrastructure, manage resource capabilities, and manage the impact of use to make Buntu Burake a sustainable tourism destination. Keywords : Carrying Capacity  of Tourism, Sustainable Tourism